Pregnant human peripheral leukocyte migration during several late pregnancy clinical conditions: a cross-sectional observational study - Takeda, Jun; Fang, Xin; Olson, David M. (BMC Pregnancy and Childbirth, 2017)
Background Parturition at term and preterm is characterized by sterile inflammatory processes occurring in the absence of infection whereby peripheral leukocytes infiltrate gestational tissues in response to chemotactic signals. In response to a homing signal, recruited leukocytes undergo diapedesis and extravasate through capillaries, migrating into stromal tissue. There they interact with resident immune and stromal cells to produce a mixture of matrix metalloproteinases, prostaglandins and cytokines including interleukin-1β (IL-1β) and IL-6 that in turn transform the uterus from pregnancy to parturition. Since migration is an early parturitional event our purpose was to study the migration of maternal peripheral blood leukocytes in response to a standard chemotactic signal during several different conditions of late pregnancy. Methods We used a cross-sectional observational study design. Subjects were (sTL) spontaneous normal labour delivered vaginally at term, (TNL) elective caesarean section at term without labour, (PTL) preterm in labour, (PTNL) preterm not in labour, (TPTL) threatened preterm labour, and (pPROM) preterm with premature rupture of membranes. Leukocytes (100,000) obtained by venipuncture and chemotactic factor isolated from term labour fetal membranes were placed in the upper and lower halves, respectively, of a Boyden chamber separated by a filter with 3μm pores. Migrated leukocytes were assessed by flow cytometry. The number of leukocytes that migrated in 90 min was the primary outcome measure. Results Increased numbers of leukocytes from peripheral blood of women in labour (TL or PTL) or soon to go into labour (PPROM) migrated towards a chemotactic signal than did leukocytes from women not in labour (TNL, PTNL, or TPTL) ( p < 0.0001). All pPROM delivered within 7d; TPTL delivered >30d. Receiver operating characteristic curve parameters indicated the cut-off point for delivery within 7d to be 37,082 leukocytes with sensitivity 78.1%, specificity 88.9%, positive predictive value 91.4%, negative predictive value 72.7%, and area under the curve 0.83. Conclusion Leukocyte migration to a fetal membrane signal varies in a predictable fashion during various clinical situations of late gestation. This principle has the potential to be improved to become a clinical test to predict delivery.